CARBONIFEROUS-PERMIAN STRATIGRAPHY AND FUSULINIDS OF EASTERNIRAN. THE PERMIAN IN THE BAG-E-VANG SECTION (SHIRGESHT AREA) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Jamal Formation of the Bag-e-Vang section near Shirgesht is described. The lower part of the formation (Bag-e-Vang Member) is composed of shales and marls with interbeds of hallow water bioclastic limestones. It contains abundant fusulinids indicative of the uppermost Yakhtashian-basal Kubergandian. The upper part of the Jamal Formation is represented by micritic and finely detrital limestones and dolomites. The age of this part of the formation is based on rare fusulinids and smaller foraminifers and cannot be defined more precisely than the Kubergandian-Dorashamian of the Upper Permian. The formation has visible conformable contacts with the underlying Sardar and overlying Sorkh Shale Formations. However, there may be unobservable stratigraphic hiatuses of indefinite scope at the formation boundaries. Forty-one species and subspecies, which belong to 27 genera and subgenera and 9 families of fusulinids, were identified in the Permian of the section described. Among them, two genera (Iranella, Paraleeina), one subgenus (Cuniculina) and 8 species, i. e. Yangchienia compressaeformis,Paradoxiella insueta, Darvasites minutus, Skinnerella chusenellaeformis, Iranella bella, I. longa, I. orbiculata, and I. pauca, are new.